Contribution of rural women to rice production activities in two different areas of Bangladesh (Progressive Agriculture, 2016)
The study was undertaken to identify the core contribution of women in the rice production activities, identify the wage gap between male and female laborer and factors influencing womens participation in rice farming at household level in Bangladesh. In doing so, the study utilized the data collected by the field survey from Nilphamari and Mymensingh districts of Bangladesh. A total number of 60 women respondents were selected using random sampling methods who were actively working in the rice fields during the production period in 2015. Data were analyzed using simple statistical techniques as well as OLS regression analysis. An analysis of the socioeconomic status of the women showed that in terms of contribution, nearly 43% and 42%of the total works were done by rural women in rice farming activities in Nilphamari and Mymensingh district, respectively. It was found that male workers spent 228.2 hours and female workers 174.5 hours per season in Nilphamari region compared to 270 hours and 197.3 hours per season in Mymensingh region, respectively. The average wage rate in Nilphamari district was BDT 241/day for male and BDT 175/day was female. Similarly, in Mymensingh district the average wage rate for male and female workers was BDT 281/day and BDT 162/day, respectively. The result of the OLS method suggests that the distance of the rice field from the home, the number of available technologies used and the number of adult male labour significantly affect the women's participation in farming activities. Despite the positive role of women in the production activities, their contribution was often neglected in terms of wage rate. Therefore, this study recommends the avoidance of wage discrimination between male and female workers which may strengthen their position within the family and increase their self-esteem and status in the society.Progressive Agriculture 27 (2): 180-188, 2016